Citra Feminitas dalam Novel Cintapucino - Meilani Tri Hapsari (KOMVERSAL, 2020)
ABSTRACT Femininity as a lifestyle appears in various domains, including novels. This study aims to determine the meaning of the image text of femininity and the myth of the image of femininity in the novel Cintapuccino through the labeling system of Roland Barthes. The research method used is structural semiotic analysis with the semiotic model of Roland Barthes which analyzes the text to the level of myth. The research data were obtained from the novel Cintapuccino produced by Gagas Media in 2004. The research subjects were focused on texts containing mythical representations of the image of femininity in women. The results showed that the image of femininity represented was the lifestyle of single women in urban areas, women's bodies in lifestyle and images of femininity, urban women's resistance in the framework of femininity, and women's obsession with marriage. The myth about women is represented through the ability to do men's work, knowledge about sex, and sexual behavior. This myth is related to the masculinity that exists in women, namely in terms of men's jobs that are able to be done by women and about knowledge about sex and sexual behavior. Key words: Image, feminine, novel, semiotic, Roland Barthes ABSTRAK Feminitas sebagai suatu gaya hidup muncul dalam berbagai domain, termasuk di dalamnya adalah novel. Penelitian ini bertujuan untuk mengetahui makna teks citra feminitas dan mitos citra feminitas dalam novel Cintapuccino melalui sistem penandaan Roland Barthes. Metode penelitian yang digunakan adalah analisis semiotika struktural dengan model semiotika Roland Barthes yang menganalisis teks sampai pada tataran mitos. Data penelitian diperoleh dari novel Cintapuccino yang diproduksi oleh Gagas Media pada tahun 2004. Subjek penelitiannya difokuskan pada teks-teks yang memuat representasi mitos citra feminitas pada perempuan. Hasil penelitian menunjukkan bahwa citra feminitas yang direpresentasikan adalah gaya hidup perempuan lajang di perkotaan, tubuh perempuan dalam gaya hidup dan citra feminitas, perlawanan perempuan perkotaan dalam kerangka feminitas, dan obsesi perempuan terhadap pernikahan. Adapun mitos tentang perempuan direpresentasikan melalui kemampuan melakukan pekerjaan laki-laki, pengetahuan seputar seks, dan perilaku seks. Mitos tersebut terkait dengan muatan maskulinitas yang ada pada perempuan, yaitu dalam hal pekerjaan laki-laki yang mampu dilakukan perempuan serta seputar pengetahuan tentang seks dan perilaku seksnya. Kata kunci : Citra, feminitas, novel, semiotika, Roland Barthes